INTERPRETATIVE UNDERSTANDING TERHADAP MAKNA SIMBOL AL-FATIHAH DALAM AMALIAH TASHARRAFUL FATIHAH PADA MASYARAKAT BANTUL, YOGYAKARTA - Imam Muhlis; Fathorrahman Fathorrahman (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2015)
Tasharruful Fatihah is one of religious rituals growing in Nahdatul Ulama (NU) surroundings at Bantul regency as a means of devotion, worship, and reverence to Allah the Almighty. This ritual recites al-Fatihah as the primary reading. This ritual procession is barely seen as a symbol of belief that it is a different method to be closer to the Almighty. The series of this ritual becomes one encouraging source for a worship movement towards Allah. This study recommends that Tasharruful Fatihah initiated by some NU leaders is an attempt of dialoguing Islam with the local culture as an inseparable unity. Nevertheless, there are fundamental differences in the source of Islamic teachings versus the source of social traditions.